2021
DOI: 10.1007/s00267-021-01446-1
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing Integrated Water Resource Management in Latin America: Insights from Application of the Freshwater Health Index

Abstract: Water crises in Latin America are more a consequence of poor management than resource scarcity. Addressing water management issues through better coordination, identification of problems and solutions, and agreement on common objectives to operationalize integrated water resources management (IWRM) could greatly improve water governance in the region. Composite indices have great potential to help overcome capacity and information challenges while supporting better IWRM. We applied one such index, the Freshwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 56 publications
(72 reference statements)
0
25
0
1
Order By: Relevance
“…However, with few exceptions, such as the European Union's Water Framework Directive, decision-makers are at an early stage in developing and integrating ecosystem services into water resource management. In apply this indicator framework under FHI (basins from Asia, Africa, and Latin America) we have found that most stakeholders, whilst familiar with the concept of water ecosystem services, have considered them less often than the bio-physical or governance aspects of water management (Vollmer et al 2018;Bezerra et al 2021;Souter et al 2020;Wen et al 2020). Furthermore, the need for monitoring and management of water ecosystem services is not yet legislated in many jurisdictions (cf Liu et al 2019).…”
Section: Focusing On Delivery Of Water Ecosystem Services As a Starting Pointmentioning
confidence: 99%
See 4 more Smart Citations
“…However, with few exceptions, such as the European Union's Water Framework Directive, decision-makers are at an early stage in developing and integrating ecosystem services into water resource management. In apply this indicator framework under FHI (basins from Asia, Africa, and Latin America) we have found that most stakeholders, whilst familiar with the concept of water ecosystem services, have considered them less often than the bio-physical or governance aspects of water management (Vollmer et al 2018;Bezerra et al 2021;Souter et al 2020;Wen et al 2020). Furthermore, the need for monitoring and management of water ecosystem services is not yet legislated in many jurisdictions (cf Liu et al 2019).…”
Section: Focusing On Delivery Of Water Ecosystem Services As a Starting Pointmentioning
confidence: 99%
“…Given the uncertainty of the dataset used for the initial assessment, it was recognized that improving data on fish harvests should be prioritized, to inform monitoring and better calibrate any modeling efforts. Bezerra et al (2021) report that, when this framework was applied in Latin America, the juxtaposition of water quality regulation and disease regulation indicators fostered discussion of their linkages. Our framework supports better and more comprehensive management of freshwater systems (ecosystems included), by providing a starting point for scrutiny and discussion.…”
Section: Focusing On Delivery Of Water Ecosystem Services As a Starting Pointmentioning
confidence: 99%
See 3 more Smart Citations